Variants in the CYP2B6 3′UTR Alter In Vitro and In Vivo CYP2B6 Activity: Potential Role of MicroRNAs. Issue 1 (25th October 2017) - Burgess, Kimberly S.; Ipe, Joseph; Swart, Marelize; Metzger, Ingrid F.; Lu, Jessica; Gufford, Brandon T.; Thong, Nancy; Desta, Zeruesenay; Gaedigk, Roger; Pearce, Robin E.; Gaedigk, Andrea; Liu, Yunlong; et al.
Abstract : CYP2B6*6 and CYP2B6*18 are the most clinically important variants causing reduced CYP2B6 protein expression and activity. However, these variants do not account for all variability in CYP2B6 activity. Emerging evidence has shown that genetic variants in the 3′UTR may explain variable drug response by altering microRNA regulation. Five 3′UTR variants were associated with significantly altered efavirenz AUC0‐48 (8‐OH‐EFV/EFV) ratios in healthy human volunteers. The rs70950385 (AG>CA) variant, predicted to create a microRNA binding site for miR‐1275, was associated with a 33% decreased CYP2B6 activity among normal metabolizers (AG/AG vs. CA/CA ( P < 0.05)). In vitro luciferase assays were used to confirm that the CA on the variant allele created a microRNA binding site causing an 11.3% decrease in activity compared to the AG allele when treated with miR‐1275 ( P  = 0.0035). Our results show that a 3′UTR variant contributes to variability in CYP2B6 activity.